A CASE REPORT ON ANTI-N-METHYL-D-ASPARTATE RECEPTOR ENCEPHALITIS - Alexander, Sherin; Kn, Anila (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Anti N-methyl-D-aspartate (NMDA) re-ceptor en-cephalitis is an immune medi-ated disorder and it is a dis-order of the limbic system that largely af-fects female children. Anti-NMDA recep-tor encephalitis was actually described as a paraneoplastic syndrome as it is associated with ovarian teratomas con-taining neural tissue with an-tibodies cross reacting to the NMDA recep-tors. Here we discuss a case of NMDA re-ceptor en-cephalitis. Keywords: Anti NMDA, Paraneoplastic Syndrome, Tera-toma.